The increased strategic importance of the High North and its security implications for Iceland - Gustav Pétursson 1979- (2009)
The melting of the Arctic ice is opening new shipping routes through the Arctic as well as making Arctic resources more accessible and thus increasing the strategic importance of the Arctic region. This change carries with it a new set of threats and risks in the dimensions of military, political, economic as well as societal and environmental security. Iceland, like other Arctic countries, must find ways to deal with the multi-dimensional security threats and risks associated with these changes. Iceland, whose greatest security threats are in the dimension of environmental, economic and societal security, can respond to these threats and risks through international cooperation with other Nordic countries, most notably Norway and Denmark as well as NATO, the European Union and the Arctic Council.